Pengaruh Penggunaan Mobile Banking dan ATM Terhadap Kinerja Keuangan pada Perusahaan Perbankan Umum yang Terdaftar di Bursa Efek Indonesia Periode 2018-2022 - Nur Hilda Apriliani Sunge; Srie Isnawaty Pakaya; Yayu Isyana D. Pongoliu (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research aims to determine the effect of Mobile Banking and ATM on Financial Performance. The approach in this research is a quantitative method with a descriptive approach. The data collected in this research is secondary data obtained by researchers via the official website www.idx.co.id of the Indonesian Stock Exchange (BEI). The population of this research is 47 banking companies registered on the IDX. Sample collection was carried out using a purposive sampling method, so the samples that met the criteria in this research were 20 banking companies. Data analysis was carried out using multiple linear regression analysis techniques using SPSS. Based on the partial T test hypothesis testing, it can be concluded that the Mobile Banking and ATM variables partially have a significant positive effect on Return on Equity and Return on Assets. Based on the simultaneous F test hypothesis testing, it can be concluded that the Mobile Banking and ATM variables simultaneously have a significant positive effect on Return on Equity and Return on Assets of general banking companies listed on the Indonesian Stock Exchange in 2018-2022.